LEAD ISOTOPE CHARACTERIZATION OF COPPER INGOTS FROM SARDINIA (ITALY): INFERENCES ON THEIR ORIGINS - Pinarelli, L. (Bulletin of the Geological Society of Greece, 2004)
The provenance of the materials making up the metal artifacts represents a fundamental question for archaeological research. The complex processes necessary to extract the metals from the minerals cause considerable changes in their chemical composition. By contrast, the ratio of the different lead isotopes in artifacts is not influenced by metallurgie processes. Therefore, the raw mineral material and the extracted metal exhibit the same isotope "footprint". Over the course of history, Sardinia has played a major role in maritime routes. Its considerably rich mineral resources, with copper, lead and iron mineralizations, moreover complemented its strategic importance. During the 10th and 9th centuries BC Sardinia, because of its strategic location, was to become directly involved in the "precolonial" Phoenician expansion. Two repositories of copper ingots recovered at different levels within a nuragic village in northwest Sardinia, can be placed within this historical context of intense traffic and exchange of goods between native Sardinian and Phoenician communities. The ingots were made in different shapes: plane-convex, biconvex, truncated cone and irregular. The analyzed ingots exhibit a considerable lead isotopie variability, although no systematic differences in isotope composition were revealed between the ingots from the two different repositories. Moreover, no systematic isotopie variations were observed between the different shapes in which the material was found. Overall, the ingots exhibit a linear distribution in the lead/lead diagrams. The group of ingots with the lowest isotope ratios project onto the area defined by the northwestern Sardinian mineralizations. The ingot located on the other extreme end of the straight line in the Pb diagrams overlaps the area defined by the southern Sardinian deposits. The isotope footprints of the intermediate samples seem to indicate that they stem from the mixing of two components from two different mining areas of Sardinia, one in the north, the other in the south. Therefore, widespread exchange of metal must have taken place throughout the island, and such an exchange does not seem to have been hindered by the advent of the Phoenicians in Sardinia. The results of the present investigation indicate that the majority of the examined ingots was produced with metal from the northwest of the island, and that these mines were therefore known and exploited in nuragic times. Such findings shed new light on the complex issues involved in proto-historic Sardinian metallurgy